Community Nursing Care For Adolescents With Depression In Sukoharjo: Case Report (HEALTH CARE: JURNAL KESEHATAN, 2026)
Depression is one of the most common mental health disorders among adolescents and can affect social functioning, academic performance, and quality of life. One non-pharmacological intervention that can be used to address depression is mindfulness therapy. This article aims to describe changes in depression levels among adolescents after receiving mindfulness therapy. The method used was community nursing care provided to seven adolescents categorized as having severe depression based on screening using the Patient Health Questionnaire-9 (PHQ-9) instrument. The intervention, in the form of mindfulness therapy, was conducted in a structured manner for two weeks, with a frequency of three sessions per week and a duration of 15–20 minutes per session. Evaluation was carried out by comparing PHQ-9 scores before and after the intervention. The results showed a reduction in depression levels among all adolescents. Before the intervention, all respondents were categorized as having severe depression, with PHQ-9 scores ranging from 20 to 24. After receiving mindfulness therapy for two weeks, PHQ-9 scores decreased to 3–6, with four adolescents categorized as not depressed and three adolescents categorized as having mild depression. The mean PHQ-9 score decreased from 21.86 to 4.43, indicating an improvement in psychological condition after the intervention. These findings suggest that mindfulness therapy has the potential to be an effective non-pharmacological intervention in reducing depression levels among adolescents and may be considered in community nursing practice. Further studies with larger sample sizes are recommended to strengthen the evidence of its effectiveness.